Program evaluation: alternative and practical guidelines - Fitzpatrick, Jody; Sanders, James (New York: Pearson, 2004)
Contents: Evaluation's basic purpose, udes, and conceptual distinctions. Origins and current trends in modern program evaluation. Alternative approaches to program evaluation.Practical guidelines for planning evaluations. Practical guidelines for conducting and using evaluations. Emerging and future settings for program evaluation
Includes bibliographical references and index
Keywords: Educational Evaluation - United States